Cote d'Ivoire : First Review Under the Three-Year Arrangement Under the Extended Credit Facility, Request for Modification of Performance Criteria, and Financing Assurances Review; Press Release. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper presents key findings of the First Review for Cote d'Ivoire under the Extended Credit Facility. Program performance at end-2011 was broadly satisfactory. All quantitative performance criteria for end-2011 were met, but the implementation of structural reforms has been mixed. Although good progress has been made to strengthen public financial management, improve the business climate, and reform the cocoa-coffee sector, action on other benchmarks for the financial and energy sectors fell short of program targets. Prospects for 2012 are favorable, notwithstanding the weak external environment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet